Embracing variety in decision-making regarding adoption of industry 4.0 - Milou Habraken; Tanya Bondarouk (Administrative Sciences, 2020)
Industry 4.0 embodies the three technology-based developmental streams currently available and is widely recognised whether it is viewed as a great step forward or not. Consequently, the interest in the topic of "implementation" regarding Industry 4.0 has grown in recent years. However, data to date depict a somewhat single (technology-push, focused on organisational benefits) way of representing the drivers of Industry 4.0 adoption. In response, this paper intends to show to the scholarly and business communities that discussions in the literature on Industry 4.0 adoption drivers do not fully reflect the Industry 4.0 reality, which seems to us to be much more diverse. In other words, the goal is to provide an overview of the breadth and variation in drivers of Industry 4.0 adoption. This is achieved through assessing eight cases selected from the Dutch national and eastern regional platform for Industry 4.0. The cross-case analysis reveals the diversity in existing Industry 4.0 adoption drivers and highlights the apparent importance of the need-pull approach. It further highlights the relevant role that appears to be played by both internal supporting resources and external parties. Finally, it emphasises the diverse possibilities that the Industry 4.0 streams create.
Keywords: 350; decision-making; Industry 4.0; integrated approach; technology adoption drivers; technology-push vs. need-pull